Gender perspective in understanding and perception of climate change - Prodović Milojković, Biljana T.; Zdravković, Danijela; Nikolić, Vesna (Sociološki pregled, 2025)
The study examines climate change from a gender perspective, analyzing how gender and marginalization shape perception and response to climate challenges. It is assumed that women, due to their more vulnerable social position, suffer specific consequences of climate change, while simultaneously showing greater proactivity in climate action. The research applies a combination of quantitative and qualitative methods, including literature review, questionnaires, as well as data and reports from relevant organizations such as the IPCC. The results show that women are disproportionately affected, especially in marginalized communities, but significantly contribute to ecological solutions. It concludes that greater inclusion of women in decision-making processes and strengthening their role through education and media support are crucial for achieving sustainable climate solutions.